Modelagem do desenvolvimento e do balanço de água no solo em trigo - Alberto, Cleber Maus (2008)
Wheat is the main winter crop in Rio Grande do Sul State. Temperature and photoperiod are the major environmental factors that control development in wheat. Wheat plants exposed to cold, non freezing temperatures induce them to enter the reproductive phase. Temperature and photoperiod response functions are used to simulate the wheat development. Developmental models are important part of water soil balance, growth and yield crop models. Thus, the objectives of this thesis were: (i) to evaluate vernalization sensitivity of some Brazilian wheat genotypes and to fit a vernalization response function for these genotypes; (ii) to determine the best temperature, photoperiod and vernalization functions to simulate wheat development with the Wang and Engel (WE) model for some Brazilian wheat genotypes; and (iii) to improve the prediction of available soil water in the soil by modifying two mechanistic models. To achieve the first objective, a factorial experiment with eight levels of vernalization (0, 7, 14, 21, 28, 35, 42 and 49 vernalization days) and six wheat genotypes were used. Also a field experiment was carried out in Santa Maria, RS, Brazil, to provide independent data on the date of developmental stages of six Brazilian wheat genotypes for evaluating the original and the modified WE model. Soil water content was determined with the gravimetric method to evaluate water balance models during three sowing dates. For those genotypes that presented some response to vernalization, response functions are presented, which can be used in models for simulating the development of Brazilian wheat cultivars with distinct vernalization requirements. The WE model simulates better the development of the Brazilian wheat genotypes using cardinal temperatures higher than original WE model and using daily maximum and minimum temperatures in the calculation of the temperature response function. The modified Campbell; Diaz water balance model is more realistic and has a greater potential for performing well in regions others than it was developed. The modified Amir; Sinclair water balance model simulates better the available soil water than the original model.